Upaya Peningkatan Self Care melalui Penyuluhan Kesehatan di RSUD Sosodoro Djatikoesoemo Bojonegoro - Prima Dewi; Reni Yuliastutik; Yusuf Efendi (Pusat Riset dan Inovasi Nasional, 2025)
Diabetes mellitus (DM) is a non-communicable disease that represents a major global health challenge, including in Indonesia. It is characterized by a persistent increase in blood glucose levels due to disruptions in insulin production or function within the body. The prevalence of diabetes mellitus has grown at an alarming rate worldwide, with projections indicating a steady upward trend in the coming decades. In Indonesia, this increase is closely linked to unhealthy lifestyle changes such as poor dietary patterns, lack of physical activity, and limited health awareness. The problem is further worsened by low public knowledge regarding the importance of early detection and effective diabetic self-management. Optimal management of diabetes requires a comprehensive approach that combines medical treatment with empowering patients to consistently practice self-care. The purpose of this community service was to examine the effectiveness of health education in improving self-care practices among DM patients at Sosodoro Djatikoesoemo Bojonegoro Regional General Hospital. The program applied a Community-Based Health Education model with participatory learning methods centered on community needs, delivered through lectures and discussions. Evaluation was conducted using pre- and post-tests with questionnaires for 25 participants. The results showed that after counseling, 60% (15 respondents) achieved good self-care. Counseling significantly enhanced diabetic self-management, as reflected in improved scores and a positive shift in categories across all assessed aspects.